The influence of board gender diversity on financial performance of listed companies in Nigeria / Armaya’u Alhaji Sani … [et al.] - Alhaji Sani, Armaya’u; Abubakar, Ibrahim Adamu; Aliyuc, Umar; Sule, Safiyanu (Accounting Research Institute (ARI), UiTM Shah Alam, 2019)
This study examined the impact of board gender diversity on the financial performance of listed companies in Nigeria. Using a sample of 400 firmyear observations for the period of 2012-2016. The data for the study were extracted from the annual reports of the sampled firms and the Thompson Reuters DataStream. The data was analysed by means of the Panel Corrected Standard Error (PCSE). The study found that gender diversity (female directors) influenced the financial performance of companies listed on the Nigerian Stock Exchange. The findings supported the argument that gender diversity enhances the financial outcomes of firms. Consistent with the Resource Dependency Theory, the result implied that female directors contribute to the upper echelon of the firm’s decision. The findings inform regulators and other stakeholders on the roles of female directors in explaining the corporate financial outcomes.